Legal Review On Agreement Between Labor With Employers Based On Act No. 13 Of 2003 Concerning Employment In Ud. (Business Trade) Endah Pratama Pati Regency - Iqbal Ghani Morotjono; Sri Herlina; Arief Cholil (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The employment agreement is an agreement made by business owners with employees. Trace Article 1 point 14 of Act No. 13 of 2003 on Labor, employment agreement is an agreement between the workers / laborers with employers which contains the terms of employment, the rights and obligations of the parties. The agreement may be written and unwritten. Unwritten agreement has the disadvantage not have the force of law when the future of a dispute between workers and employers. In this case related to the employment relationship between employers and employees in UD. Endah Pratama Pati regency, Central Java.This study aims to find out how conduciveness workers in a company that does not implement a written agreement for workers. And how treatment can be done if the aggrieved party both employers and workers.UD leaders of Endah Pratama with workers can be said to be communicative in terms of implementation of the work. Although the company already provides rights and obligations of workers, slow lorises future still does not close a dispute in matters of workKeywords: Employment Agreement; No Written Agreement; Rights And Obligations Of Workers Act No. 13 of 2003 on Manpower.